Assessing youth's behaviour towards sustainability in overpackaging of e-commerce purchases in Klang Valley - Md Jusoh, Zuroni; Noor Hizam, Nor Farisha (Labuan Faculty of International Finance and UMS Press, 2024)
This research investigates the behaviour of youths in the Klang Valley regarding overpackaging in e-commerce purchases. The finding demonstrated that environmental concern emerges as a pivotal factor, with the highest mean score, indicating a heightened awareness of the long-term consequences of excessive packaging on the environment. Pearson correlation analyses reveal a significant positive relationship between attitude and behaviour, underscoring the impact of positive attitudes on shaping consumer behaviour. Subjective norms exhibit a substantial positive correlation, emphasizing the influence of perceived social norms. Perceived behavioural control demonstrates a robust positive relationship, indicating the influential role of individuals' beliefs in shaping their behaviours. The study also finds a moderate but significant relationship between environmental concern and behaviours, highlighting the importance of heightened environmental awareness in promoting sustainable consumer behaviour. The MLR analyses emphasized the influential role of attitudes, subjective norms, and perceived behavioural control in shaping behaviours, with environmental concern playing a crucial but nuanced role. The findings provide valuable insights for policymakers and businesses aiming to foster sustainable behaviour in e-commerce.